Improving the Quality of Teacher Training for the Organization of Dialogic Education of Primary School Students: Methodical Aspect - Fomin, Kateryna; Boiko, Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article presents organizational and methodological aspects of professional training of future primary school teachers for dialogic learning of students. Dialogic learning is a kind of interactive organization of the educational process, based on mutual understanding and interaction, considered by the author as an effective factor of improving professional future primary school teachers’ skills. The organizational aspects of the effective practical solution of the researched problem are outlined, such as dialogization of the content of education; introduction of various forms of productive dialogues and a system of methods of problem-based learning; dialogization of communication as a means of creation a certain psycho-emotional educational microenvironment; formation of future specialists’ skills of critical reflection as an internal dialogue for self-improvement and self-development. The pedagogical potential of the disciplines of psycho-pedagogical and professional-methodical orientation on the dialogue of the educational process is determined. It has been proved that effective forms and methods of dialogic learning in teacher training are: training, group activities, problem lectures, interactive classes, discussions, didactic games, business- and role-playing games, etc. The basic principles of pedagogical ethics and culture of the organization of dialogic training within the study of an elective course “Communicative Pedagogy” are emphasized. It was found that the quality of dialogic learning is determined by the level of formation of participants’ communicative competence in pedagogical interaction, especially their mastery of the basic techniques of listening. The author’s materials from the dissertation “Preparation of primary school teachers for the organization of dialogic training” for PhD (K. Fomin, 2020) are partially used in the article.